A metaficção historiográfica na literatura goiana: dois autores, duas obras - Borges, Patrícia Espíndola (2009)
This essay aims to discuss the historiography metafictional in the books A Casca da Serpente, by José J. Veiga and Sete Léguas de Paraíso , by Antônio José de Moura, based on theoretical studies of Hayden White, George Lukács, Linda Hutcheon and Aristóteles, among others. Initially, discuss the conception of history and literature and their respective discourse. Then make a soon evolution of the novel, emphasizing the similarities and distinctions between the historical novel, and historiography metafiction. To be Worth to the features of this, especially the parody, irony and eccentricity, to analyze the novels selected in order to prove that the discourse historiography metafictional recurs in their plots, A Casca da Serpente , and Sete Léguas de Paraíso . Complementing this interpretation, we resorted to some aspects of symbolic and metaphorical in order to enhance and strengthen the proposed objectives. He drew a parallel between the narratives of the active corpus with reference to the theory explained by Bakhtin in Problems of Dostoevsky's poetics. At the end of the study, emerged as the literature has the power to subvert the story, transforming it into other discourses, making it take a new look, taking the reader to reflect and challenge the components of historiography discourse.